Risk factors in EBR students during confinement by COVID19: review of family prevention measures in Peru - Rivas Meza, Alexandra (2022)
This thesis was proposed with the objective of collecting the main resources of an educational, socio-educational and psychological nature for families in confinement due to COVID-19, at two levels: - Identify the existing resources in the Peruvian state concerning educational support, socio-educational and psychological against the isolation applied by coronavirus. Likewise, to identify the main risks in students of the EBR that emerged during confinement and include the reference strategies, at an international level, to improve and/or maintain family dynamics, which allow preventing the risks of confinement in Peru, since the On March 15, 2020, the Peruvian government declared a state of health emergency prompted by the rapid evolution of SARS-Cov-2. as a family care measure to face the COVID-19 pandemic. The greatest impact of the restrictions applied due to the lack of contact with the main  spheres of socialization has been in childhood and adolescence. The increase in the rates of family violence and the abusive consumption of the game show the need to reinforce family prevention measures. Consequently, a large part of Peruvian prevention measures is of a tertiary nature. It should be noted that there is still a need to provide resources for primary risk prevention, aimed at improving family communication and parental skills in order to reduce the rates of family violence and the inappropriate use of ICT by children and adolescents.